Melbourne 1956 . Melbourne 1956 - Sibalin, György (Hungary, 2004)
A film about the journey of the Hungarian Olympic team to the 1956 Olympic Games in Melbourne. While the country was burning with revolution followed by heavy Soviet retaliation, the Hungarian team managed to win 9 gold medals. Most of them however never returned to Hungary.